2019
DOI: 10.1002/advs.201802289
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of Nanomaterials to Eyes: An Important but Neglected Issue

Abstract: The production and application of nanomaterials have grown tremendously during last few decades. The widespread exposure of nanoparticles to the public is provoking great concerns regarding their toxicity to the human body. However, in comparison with the extensive studies carried out to examine nanoparticle toxicity to the human body/organs, one especially vulnerable organ, the eye, is always neglected. Although it is a small part of the body, 90% of outside information is obtained via the ocular system. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 170 publications
0
81
0
Order By: Relevance
“…NPs, with smaller diameters and larger surface areas, are suspended for longer in the air and result in more harm to the public 5,6 . A large number of studies have found that widespread exposure to NPs is nocuous to the main organs of humans, such as the respiratory tract, skin, brain, lungs, and immune system [7][8][9][10] , leading to neuroinflammation and decreased cognitive abilities, even causing a DNA damage [11][12][13][14][15] . According to an analysis of the Global Burden of Disease Study 2017 (ref.…”
mentioning
confidence: 99%
“…NPs, with smaller diameters and larger surface areas, are suspended for longer in the air and result in more harm to the public 5,6 . A large number of studies have found that widespread exposure to NPs is nocuous to the main organs of humans, such as the respiratory tract, skin, brain, lungs, and immune system [7][8][9][10] , leading to neuroinflammation and decreased cognitive abilities, even causing a DNA damage [11][12][13][14][15] . According to an analysis of the Global Burden of Disease Study 2017 (ref.…”
mentioning
confidence: 99%
“…Many studies have extensively evaluated the toxicity of nanoparticles on main organs, whereas only a few studies have examined the potential toxicity of nanomedicine regarding their exposure time or size on the eye. 75 Furthermore, each nanoparticle has unique physiochemical properties including chemical composition, surface area, and charge that can affect its toxicity on the eye. 75,76 Various biological models have been utilized for determining potential toxicity of nanoparticles in the eyes.…”
Section: Nanomedicine As Novel Drug Delivery Systemmentioning
confidence: 99%
“…75 Furthermore, each nanoparticle has unique physiochemical properties including chemical composition, surface area, and charge that can affect its toxicity on the eye. 75,76 Various biological models have been utilized for determining potential toxicity of nanoparticles in the eyes. Most biological models (including in vitro and in vivo models) when treated with inorganic nanoparticles exhibited oxidative stress and damaged ocular system.…”
Section: Nanomedicine As Novel Drug Delivery Systemmentioning
confidence: 99%
“…22 However, considering that retinal toxicity is a major concern when administering drugs and materials intravitreally, it is important to assess the safety of new drug delivery systems by different assays, in order to assure their safety. 23,24 Furthermore, the mechanisms of toxicity resulted from nanomaterials in the eyes is different from other materials, requiring more attention when investigating these carriers, which has been neglected in many studies. 24…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Furthermore, the mechanisms of toxicity resulted from nanomaterials in the eyes is different from other materials, requiring more attention when investigating these carriers, which has been neglected in many studies. 24…”
Section: Introductionmentioning
confidence: 99%